2014
DOI: 10.3892/or.2014.3452
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effect of ginsenoside Rg3 and cisplatin in cisplatin-resistant bladder tumor cell line

Abstract: Abstract. Cisplatin-based chemotherapy is the first-line treatment for metastatic urothelial cell carcinoma. However, for cisplatin-resistant cases, no chemotherapeutic agent has been established as a standard of treatment. This study aimed to investigate the synergistic antitumor effect of ginsenoside Rg3 on cisplatin in cisplatin-resistant bladder cancer cells (T24R2). T24R2 cells were treated with cisplatin and/or ginsenoside Rg3. Cell viability was assessed by the Cell Counting Kit-8 and clonogenic assays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Preclinical studies have indicated that ginsenoside Rg3 is able to exert anticancer effects by inhibiting angiogenesis and tumor growth in many solid tumors such as hepatocellular carcinoma [18], bladder cancer [19], breast cancer [20], ovarian cancer [21] and colorectal cancer [22]. A previous study has also shown the inhibitory effect of ginsenoside Rg3 combined with gemcitabine on the growth of lung cancer in mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have indicated that ginsenoside Rg3 is able to exert anticancer effects by inhibiting angiogenesis and tumor growth in many solid tumors such as hepatocellular carcinoma [18], bladder cancer [19], breast cancer [20], ovarian cancer [21] and colorectal cancer [22]. A previous study has also shown the inhibitory effect of ginsenoside Rg3 combined with gemcitabine on the growth of lung cancer in mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…Most research papers cited in this review were focused solely on the mechanisms of action and the efficiency of combined saponin/drug use, and these concerned mainly dammarane‐type saponins such as ginsenosides isolated from Panax sp. (Lee et al, ; Park et al, ; Wang et al, ; Yang et al, ; Zhang et al, ; Zhang et al, ; Zhang & Li, ). However, it is not possible to draw any conclusions concerning the potential SAR.…”
Section: Structure–activity Relationship In Combined Therapymentioning
confidence: 99%
“…Tubeimoside I, isolated from the tubers of Bolbostemma paniculatum (Cucurbitaceae), exerts an antiproliferative effect and sensitizes human ovarian cancer A2780/DDP cells to S. M. Kim et al (2009Kim et al ( , 2010 cisplatin by inducing apoptosis, down-regulating ERK1/2, and upregulating p38 signaling pathways . Likewise, ginsenoside Rg 3 inhibits the proliferation of cisplatin-resistant bladder cancer cells (T24R2) in a synergistic manner with cisplatin (Lee et al, 2014). Combined treatment (cisplatin and ginsenoside Rg3) activates the intrinsic apoptotic pathway and enhances cell cycle alteration.…”
Section: Triterpene Saponins and Cisplatinmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely used as a traditional medicine because of its health benefits. Several studies have demonstrated the beneficial effects of ginseng, such as blood circulation improvement, blood cholesterol improvement, anti‐diabetic (Kang, Lee, Ahn, & Lee, ; Qi, Wang, & Yuan, ; Yuan, Kim, Kim, & Chung, ), neuroprotective activity, memory improvement, anti‐inflammatory (González‐Burgos, Fernandez‐Moriano, & Gómez‐Serranillos, ), anticancer activity (Ahuje, Kim, Kim, Yi, & Cho, ; Lee et al, ; Xu et al, ), anti‐fatigue, anti‐stress effects, immune function improvement (So, Lee, Kim, Hyun, & Han, ; Wang et al, ), and anti‐aging effects (Bjorklund et al, ). Moreover, ginseng is also known to increase vitality, health, and longevity, especially in elderly people (Yang, Ren, Zhang, & Wu, ).…”
Section: Introductionmentioning
confidence: 99%